Trauma as common denominator of sexual violence and victimisation - Veselinović Nataša I. (Temida)
Results of researches on biological, psychological and sociological characteristics of sexual offenders show etiological and phenomenological differences, while, on the other side, treatment programs show tendency toward unification. Unification that works contains behavioural learning victim empathy work and work on one’s own trauma. In this paper the author looks for an answer to the question who is the sexual offender and how he became that. In theory rapists and paedophiles are similar as much as their victims are, and they are often victims of some traumatic experience which seeks for satisfaction in inappropriate but well-known way. Sexual violence can be stopped by breaking the circle of its beginning and development by helping sexual perpetrator to find the way out from sexual violence circle and healthier behavioural patterns.